Borderline personality disorder and the big five: molecular genetic analyses indicate shared genetic architecture with neuroticism and openness - Streit, Fabian; Witt, Stephanie; Awasthi, Swapnil; Foo, Jerome Clifford; Jungkunz, Martin; Frank, Josef; Colodro-Conde, Lucía; Hindley, Guy; Smeland, Olav B.; Maslahati, Tolou; Schwarze, Cornelia E.; Dahmen, Norbert; et al. (Translational Psychiatry, 2022)
Both environmental (e.g. interpersonal traumatization during childhood and adolescence) and genetic factors may contribute to the development of Borderline Personality Disorder (BPD). Twin studies assessing borderline personality symptoms/features in the general population indicate that genetic factors underlying these symptoms/features are shared in part with the personality traits of the Five Factor Model (FFM) of personality—the “Big Five”. In the present study, the genetic overlap of BPD with the Big Five -Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism- was assessed. Linkage disequilibrium score regression was used to calculate genetic correlations between a genome-wide association study (GWAS) in central European populations on BPD (N = 2543) and GWAS on the Big Five (N = 76,551-122,886, Neuroticism N = 390,278). Polygenic scores (PGS) were calculated to test the association of the genetic disposition for the personality traits with BPD case-control status. Significant positive genetic correlations of BPD were found with Neuroticism (rg = 0.34, p = 6.3*10−5) and Openness (rg = 0.24, p = 0.036), but not with the other personality traits (all | rg | <0.14, all p > 0.30). A cluster and item-level analysis showed positive genetic correlations of BPD with the Neuroticism clusters “Depressed Affect” and “Worry”, and with a broad range of Neuroticism items (N = 348,219-376,352). PGS analyses confirmed the genetic correlations, and found an independent contribution of the personality traits to BPD risk. The observed associations indicate a partially shared genetic background of BPD and the personality traits Neuroticism and Openness. Larger GWAS of BPD and the “Big Five” are needed to further explore the role of personality traits in the etiology of BPD.
Gesehen am 26.03.2024